40Ar–39Ar dating and tectonic implications of volcanic rocks recovered at IODP Hole U1342A and D on Bowers Ridge, Bering Sea. (March 2016) - Sato, Keiko; Kawabata, Hiroshi; W. Scholl, David; Hyodo, Hironobu; Takahashi, Kozo; Suzuki, Katsuhiko; Kumagai, Hidenori
Abstract: During the Integrated Ocean Drilling Program (IODP), a total of 41.54 m of basement rock, consolidated volcaniclastic sediment, was recovered beneath a thin sediment cover. The drilled site is at the eastern end of the crestal area of Bowers Ridge, a north and westward sweeping offshoot of the Aleutian Arc into the Bering Sea. The volcanic sequence recovered from Holes U1342A and U1342D was divided into six major lithologic units. We used the single grain 40 Ar– 39 Ar dating method performed by step-wise heated laser fusion technique to date andesites of Unit 1. Thereby two ages of Oligocene volcanism (34–32 Ma, 28–26 Ma) were distinguished each other according to our 40 Ar– 39 Ar data. These ages refute a hypothesized Cretaceous origin in the North Pacific as an exotic arc massif or sector of the Hawaiian-Emperor chain and indicate that the Bowers Ridge is a Bering-Sea formed arc or remnant arc that ceased forming in the latest Oligocene to the earliest Miocene time.